2016
DOI: 10.5114/ceji.2015.56969
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in Nigerians with tubal infertility

Abstract: IntroductionImmune response to genital Chlamydia trachomatis infection is involved in both immunity and pathology. The cytokine profile during infection has been implicated in the disease outcome, either resolution or severe sequelae. Serum cytokines of Chlamydia positive Nigerian women with tubal infertility were assessed to determine their possible relationship with tubal occlusion.Material and methodsOne hundred and fifty age-matched consenting women (100 fertile and 50 with tubal infertility) were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…IL-10 is known to selectively suppress the production of different inflammatory cytokines, whose effects are needed to eradicate C. trachomatis infection [16]. Higher IL-10 levels were seen in infertile woman [17] and other studies found this cytokine to be associated with susceptibility and typical pathological changes caused by the genital Chlamydia infection such as granuloma formation and fibrosis [18]. Higher IL-10 levels in woman may be associated with tubal pathology and may be responsible for their failure to eradicate genital Chlamydia infection and the associated pathology.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is known to selectively suppress the production of different inflammatory cytokines, whose effects are needed to eradicate C. trachomatis infection [16]. Higher IL-10 levels were seen in infertile woman [17] and other studies found this cytokine to be associated with susceptibility and typical pathological changes caused by the genital Chlamydia infection such as granuloma formation and fibrosis [18]. Higher IL-10 levels in woman may be associated with tubal pathology and may be responsible for their failure to eradicate genital Chlamydia infection and the associated pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N‐nitrosamines caused severe inflammations and consequently increased the levels of cytokines, tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1 α) and interleukin 1 beta (IL‐1 β) cytokines in the male reproductive tract (testis, epididymis and sperm) . Also, Chlamydia positive women with tubal infertility have higher IL‐10 than controls, which may contribute to their development of tubal pathology . Moreover, oxidative stress caused apoptosis in testes and DNA damage in the sperms …”
Section: Discussionmentioning
confidence: 99%
“…In China, approximately 7–10% of couples of childbearing age are confronted with infertility, which is clinically defined as the failure to achieve a pregnancy after one year or more of regular unprotected sexual intercourse [ 1 ]. In recent years, the incidence of fallopian tubal sterility has increased and become one of the most common factors leading to infertility [ 2 ]. At present, the most common methods for investigating tubal patency are laparoscopy and dye laparoscopic chromopertubation, X-ray hysterosalpingography (HSG), and hysterosalpingo-contrast sonography (HyCoSy) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%